Implementation of Input Cost Standards in Budget Preparation at the Housing Provision Implementation Center of West Nusa Tenggara Province, Ministry of Public Works and Public Housing - Fathiah Rahman (Penerbit Jurnal Indonesia, 2026)
This study aims to see to what extent Standard Input Costs (SBM) can streamline costs and act as a controller in budget preparation. The method used in this study is descriptive qualitative with data sourced from secondary data and a brief explanation from one of the employees of the NTB Province Housing Provision Implementation Center, Ministry of PUPR regarding the implementation of SBM as a standard in budget preparation. The results of the study show that Standard Input Costs (SBM) cannot fully be used as a basis for budget preparation because unit costs are sourced from: a. PMK SBM and b. Market prices and those that increase income must be approved by the Minister of Finance.